BENEFITS OF USING THE TEST PYRAMID IN A MOBILE APPLICATION - Lima, Dylan Pacheco de Castro; Leal , Edson Demetrio; Mesquita, Leonardo José da Silva (Revista Interface Tecnológica, 2023)
The software testing tools and processes have proven to have high performance and security, as well as high levels of user satisfaction. This led many software development companies and researchers to believe that testing tools were a necessary part of software development. They realized that software testing tools were not simply a trend; they are a reality that software development companies of all sizes must accept. While there are many testing tools and processes, it is impossible to declare any one as the most efficient; a set of tools and processes is needed to deliver the greatest possible test coverage. That is why this paper researched common testing tools that improve the efficiency of the testing process. The objective of this study is to show test tools, present their applications and highlight the gains that their application can bring to organizations. We conclude that the test pyramid is a complete and efficient testing methodology to be executed in mobile applications and that its inclusion in the organization's processes brings several gains.
Keywords: Test pyramid; Mobile applications; Efficiency